Holocene mammal extinctions in the Carpathian Basin: a review. (29th May 2016) - Németh, Attila; Bárány, Annamária; Csorba, Gábor; Magyari, Enikö; Pazonyi, Piroska; Pálfy, József
Abstract: Mammals are a key target group for conservation biology. Insights into the patterns and timing of and driving forces behind their past extinctions help us to understand their present, and to predict and mitigate their future biodiversity loss. Much research has been focused on the intensely debated megafaunal extinctions at the Pleistocene–Holocene transition, whereas the Holocene mammal extinctions have remained less studied. Here, we consider the Holocene extinctions of mammal taxa in the Carpathian Basin, a distinctive and biogeographically well‐constrained predominantly lowland region in Central Europe. For the first time, we combine data from palaeontological, archaeozoological, and historical sources for a comprehensive analysis. A total of 11 mammal species, including steppe‐dwelling rodents, large carnivores and herbivores, disappeared from the Carpathian Basin during the Holocene. The extinctions are interpreted in the framework of changing habitats and ecosystems, as grasslands and open forests vanished at the westernmost limits of the Eurasian steppe. The temporal distribution of extinctions is non‐random; most taxon range terminations are concentrated around two discrete events. Members of the steppe community disappeared between 5000 and 4000 BP, around the Copper Age–Bronze Age transition. Large herbivores that found refugia in the forests vanished later, between the 16th and 18th centuries AD. The steppe, forest‐steppe ecosystems of the Carpathian Basin suffered a considerable loss in their mammalian fauna, which has significant implications for conservation efforts for the existing similar dry, open habitats in western Eurasia. Further research and better age constraints are needed to establish the causes of extinctions more firmly, but the lack of synchronous and severe climate and vegetation changes and the coincidence with transformations in human history suggest the prime role of anthropogenic disturbance. We conclude that there were two waves of Holocene mammal extinctions of megafaunal character in the Carpathian Basin.